Relationship Between Health Literacy and Unhealthy Lifestyle Behaviours in Older Adults Living in Switzerland: Does Social Connectedness Matter? - Maud Wieczorek; Maud Wieczorek; Clément Meier; Clément Meier; Clément Meier; Matthias Kliegel; Matthias Kliegel; Jürgen Maurer; Jürgen Maurer (Frontiers Media S.A., 2023)
Objectives: To investigate the association between health literacy (HL) and unhealthy lifestyle behaviours and to explore the moderating role of social connectedness in this relationship in older adults in Switzerland.Methods: We used data from 1,455 respondents to Wave 8 of the Survey of Health, Ageing, and Retirement in Europe (SHARE). Associations between the number of unhealthy lifestyle behaviours (smoking, risky alcohol consumption, suboptimal daily consumption of fruits/vegetables, lack of vigorous physical activity) and HL were examined using multivariable Poisson regression models, which allowed for interactions between HL and social connectedness to test the moderation hypothesis.Results: Respondents with inadequate HL were significantly more likely to have a higher number of unhealthy lifestyle behaviours than respondents with sufficient HL. We found a stronger positive association between inadequate HL and the number of unhealthy lifestyle behaviours among socially isolated individuals.Conclusion: Greater social connectedness seems to buffer the negative impact of inadequate HL on unhealthy lifestyle behaviours in older adults, highlighting the importance of good HL for healthy lifestyles, especially in individuals with low social reserve.